Whole, half and peak running demands during club and international youth rugby league match-play. Issue 1 (2nd January 2019) - Whitehead, Sarah; Till, Kevin; Weaving, Dan; Hunwicks, Richard; Pacey, Rob; Jones, Ben
ABSTRACT: Objectives: To quantify, and compare, the whole- half- and peak-match running demands of professional club and international under-16 rugby league match-play.Methods: Four professional Club (n = 30) and two International (n = 23) under-16 matches were analysed using 10-Hz micro-technology units, with players analysed according to positional groups. Absolute (m) and relative (RD; m.min –1 ) total, high speed (>5 m·s –1 ; HSR) and sprint (>7 m·s –1 ) distance were analysed for whole- and half-match alongside maximum velocity (VMAX; m.s –1 ). Peak running demands were determined via moving averages of RD for 10, 30, and 60- to 600-seconds.Results: International forwards had most likely higher whole match relative sprint and VMAX, and 1st half RD than club level, and had very likely higher peak running demands at 60-, 180- and 600-second durations. For backs, whole game RD was most likely higher and total and sprint distance was likely higher at club level matches. Peak RD was also very likely higher for club backs at 10- and 60-seconds.Conclusions: The running demand differences between club and international level at the under-16 age group are position dependent, with greater running demands at club level match play for backs, but at the international level of forwards.